Why do people migrate? : labour market security and migration decisions - Duszczyk, Maciej (Bingley, U.K. : Emerald Publishing Limited, 2019)
Migration is presently a topic that arouses universal interest. Why people choose to migrate is a question that sparks great discussion. Both economic and non-economic factors contribute to this monumental decision. This book, written by experts in the field, focuses on the issue of impact of the expected labour market security on migration decision-making. The idea of push factors such as low levels of security in the state of origin and pull factors such as the expectations of financial security are explored in depth. Another layer of analysis is added as the authors explore how the expected labour market security level may be achieved in various ways. Some migrants may choose a state with a model characterised by extensive legislation related to labour market security, while others will be more willing to choose countries with greater flexibility, where it is as easy to lose a job as to find one and have greater employment security. By providing the most recent research on the impact of labour market security on migration-related decisions, this important text will help not only answer the question of why people decide to migrate, but also uncover the decision-making process in choosing a specific receiving state. By using case studies from around Europe, this book will prove invaluable for researchers, leaders and policy makers in the field of politics and migration studies.
Introduction / Maciej Duszczyk -- Chapter 1. Labour market security and migration related decisions: theoretical background / Maciej Duszczyk, Kamil Matuszczyk -- Chapter 2. Are the countries different? statistical view on labour market security / Kamil Matuszczyk -- Chapter 3. Why and where : labour market security as a push-pull factor / Maciej Górecki, Kamil Matuszczyk, Monika Stec -- Chapter 4. Migration policy : recommendations for sending and receiving countries / Maciej Duszczyk -- Conclusion / Maciej Duszczyk.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Labor mobility -- European Union countries; Labor market -- European Union countries; Business & Economics -- Labor; Labour economics